Office Interior Atmosphere And Its Influence on Employee Retention and Work Efficiency: A Case Study of a New Venture Medical Device Company - Yulia Ridha Missmita Sappewali; Mahendra Wardhana (Green Publisher Indonesia, 2025)
New venture companies often face challenges in maintaining employee retention and optimizing work efficiency. One critical yet often overlooked factor is the role of interior design in shaping office atmosphere, which significantly influences employees’ psychological responses and performance. This study aims to examine how the interior design of PT. Kusuma Sukses Makmur, a newly established medical device company in Sidoarjo, Indonesia, affects employees’ resilience in facing work-related pressure and its impact on task completion efficiency. The research applies a mixed methods approach with a sequential explanatory design. Quantitative data were first collected through Likert-scale questionnaires distributed to seven administrative employees who had worked for a minimum of six months. This was followed by semi-structured interviews to deepen the interpretation of statistical results. The research investigates how interior elements—including lighting, color, layout, materials, acoustics, and ventilation—contribute to the creation of an atmosphere that influences employee behavior. The findings show that a well-designed office atmosphere, especially one featuring natural lighting, good acoustics, and ergonomic layout, plays a significant role in enhancing emotional stability and focus. This ultimately supports employees’ resistance to stress and increases work efficiency. The study concludes that integrating atmospheric theory into office design strategies is crucial for new ventures in building a productive and emotionally supportive workplace.